The impact of the relationship between internal trade indicators and GDP growth - قصيري غدير; بشماني شكيب (Latakia University Journal - Economic and Legal Sciences Series, 2022)
Internal trade statistics constitute one of the subject areas in economic statistics, and provide data whose mission is on economic units whose main activity is concentrated in wholesale and retail trade (i.e. selling without any transfers) of any type of commodities combined. The growing interest in internal trade statistics is due to the steady increase in the contribution of internal trade to the entire national economy, hence this research, which included the relationship between internal trade indicators and growth in GDP. The research reached the following results: - One of the indicators of internal trade had an impact on the gross domestic product, which is salaries and wages, and in the short term only - There is no effect of internal trade indicators on the per capita GDP